2020
DOI: 10.1016/j.matchemphys.2020.123462
|View full text |Cite
|
Sign up to set email alerts
|

Structural, dielectric, electrocaloric and energy storage properties of lead free Ba0.975La0.017(ZrxTi0.95-x)Sn0.05O3 (x = 0.05; 0.20) ceramics

Abstract: A-site deficient Ba0.975La0.0170.0085(ZrxTi0.95-x)Sn0.05O3 (x = 0.05; 0.20) ceramics (BLaZ100xTS) were synthesized using the solid-state reaction. The microstructural study revealed a high density and low porosity in the studied ceramics. Besides, grain size lower than 1.5 µm was observed in the studied compounds, which is due to the incorporation of the rare earth element (lanthanum). X-ray diffraction and Raman studies revealed that BLaZ5TS and BLaZ20TS crystallize in a perovskite-type structure with tetrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 67 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, the ECE of our sample at 40 kV cm À1 (DT ¼ 0.986 K and z ¼ 0.245 K mm kV À1 at 363 K) is larger than that obtained for the Ba 0.65 Sr 0.35 TiO 3 ceramic by a spark plasma sintering process (DT ¼ 0.328 K and z ¼ 0.164 K mm kV À1 at 303 K) as stated by Liu et al 75 Furthermore, Patel et al 76 elaborated the Ba 0.85 Ca 0.075 Sr 0.075 Ti 0.90 Zr 0.10 O 3 ceramic by the conventional solid-state method, revealing that the ECE response reached high values of 1.6 K and 0.405 K mm kV À1 for DT and z, respectively, under 39.5 kV cm À1 at room temperature. Smail et al 66 reported ECE properties (DT ¼ 0.24 K and z ¼ 0.20 K mm kV À1 at 338 K) at a low electric eld of 12 kV cm À1 in Ba 0.975 La 0.017 (Zr 0.05 Ti 0.90 ) Sn 0.05 O 3 ceramics synthesized by solid-state reaction. These differences can be attributed to the synthesis conditions (such as calcination and sintering), chemical doping, grain shape, the number of the coexisting phases as well as the applied external electric eld.…”
Section: The Electrocaloric Effect In Bczt Ceramicsmentioning
confidence: 99%
“…Nevertheless, the ECE of our sample at 40 kV cm À1 (DT ¼ 0.986 K and z ¼ 0.245 K mm kV À1 at 363 K) is larger than that obtained for the Ba 0.65 Sr 0.35 TiO 3 ceramic by a spark plasma sintering process (DT ¼ 0.328 K and z ¼ 0.164 K mm kV À1 at 303 K) as stated by Liu et al 75 Furthermore, Patel et al 76 elaborated the Ba 0.85 Ca 0.075 Sr 0.075 Ti 0.90 Zr 0.10 O 3 ceramic by the conventional solid-state method, revealing that the ECE response reached high values of 1.6 K and 0.405 K mm kV À1 for DT and z, respectively, under 39.5 kV cm À1 at room temperature. Smail et al 66 reported ECE properties (DT ¼ 0.24 K and z ¼ 0.20 K mm kV À1 at 338 K) at a low electric eld of 12 kV cm À1 in Ba 0.975 La 0.017 (Zr 0.05 Ti 0.90 ) Sn 0.05 O 3 ceramics synthesized by solid-state reaction. These differences can be attributed to the synthesis conditions (such as calcination and sintering), chemical doping, grain shape, the number of the coexisting phases as well as the applied external electric eld.…”
Section: The Electrocaloric Effect In Bczt Ceramicsmentioning
confidence: 99%
“…(c, d) Comparison of energy storage density and energy storage efficiency of different BNT-BT5-SZ100 x ceramics at 60 kV/cm. (e) Comparison of EC coefficient (|Δ T |/Δ E ) and ξ (%) ( W rec /Δ E × 100%) achieved in this work and other bulk systems (BNT-based, ,,, BT-based, KNN-based, ,, BF-based) reported previously. (f) Directly recorded ECE signal for BNT-BT5-SZ3 ceramics under different electric fields.…”
Section: Results and Discussionmentioning
confidence: 75%
“…Additionally, in Figure e, we drafted the data points of EC coefficient (|Δ T |/Δ E ) and ξ (%) in this work and other bulk systems. It can be seen that BNT-BT5-SZ5 ceramic has a much higher ξ (1.45% J/(kV cm 2 ) at 30 °C, 1.92% J/(kV cm 2 ) at 120 °C) than those of other lead-free ferroelectric ceramics (ξ are around 0.67–1.98% J/(kV cm 2 ), 0.22–0.68% J/(kV cm 2 ), 0.34–0.57% J/(kV cm 2 ), and 1.16% J/(kV cm 2 ) for Bi 0.5 Na 0.5 TiO 3 (BNT)-based, ,,, BaTiO 3 (BT)-based, K 0.5 Na 0.5 NbO 3 (KNN)-based, ,, and BiFeO 3 (BF)-based ceramics, respectively). Therefore, our work provides a new composition, which has a good potential to achieve even higher low-field-induced energy storage density.…”
Section: Results and Discussionmentioning
confidence: 93%
“…In this regard, a universal industrial restriction has recently been adopted regarding the use of toxic materials. 16 Therefore, the need to develop materials which are both efficient and environmentally friendly has become an important alternative that is attracting a lot of attention. For example, Ba(Zr x Ti 1− x )O 3 (BZT) based ceramics have received a lot of attention for many decades due to their excellent dielectric, ferroelectric, electromechanical and piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%